Children and the Remaining Gender Gaps in the Labor Market - Patricia Cortes; Jessica Pan (Institute of Labor Economics (IZA), 2020)
The past five decades have seen a remarkable convergence in the economic roles of men and women in society. Yet, persistently large gender gaps in terms of labor supply, earnings, and representation in top jobs remain. Moreover, in countries like the U.S., convergence in labor market outcomes appears to have slowed in recent decades. In this article, we focus on the role of children and show that many potential explanations for the remaining gender disparities in labor market outcomes are related to the fact that children impose significantly larger penalties on the career trajectories of women relative to men. In the U.S., we document that close to two-thirds of the overall gender earnings gap can be accounted for by the differential impacts of children on women and men. We propose a simple model of household decision-making to motivate the link between children and gender gaps in the labor market, and to help rationalize how various factors potentially interact with parenthood to produce differential outcomes for men and women. We discuss several forces that might make the road to gender equity even more challenging for modern cohorts of parents, and offer a critical discussion of public policies in seeking to address the remaining gaps.
Keywords: J16; J24; J31; J13; 330; labor market; children; gender gap; gender